2013
DOI: 10.1002/cbdv.201200341
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Biological Studies of Phenanthroline Compounds: Selective Recognition of Gene‐Promoter G‐Quadruplex DNAs Preferred over Duplex DNA

Abstract: G-Quadruplex DNA formed in the promoter regions of proto-oncogenes would block the transcription process and eventually suppress the development of tumors, so compounds that stabilize G-quadruplex DNA are potential antitumor drugs. This article describes the interactions of three phenanthroline compounds, a-c, with proto-oncogene c-kit2 and c-myc G-quadruplex DNAs by means of polymerase chain reaction (PCR) stop assay, fluorescence resonance energy transfer melting (FRET melting) assay, fluorescence indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The similar effect was observed for F-c-myc-T and F-c-kit2-T G4 under the same conditions, and the respective ΔT m value is 8.9 and 7.5 °C when Circular dichroism (CD) CD spectroscopy is a perfect technique in investigating the secondary structural changes of DNA. [33] Both c-myc and c-kit2 have a positive peak at 264 nm and a negative peak at 241 nm in 10 mM Tris-HCl buffer containing 100 mM K + at pH 7.0 (Figure S9), which belongs to the parallel G4 structure, [34,35] while bcl-2 has an additional shoulder peak at 295 nm (Figure 5A), which is consistent with the reported mixed-type G4 structure. [36] When different concentrations of compounds are added, CD spectra of three G4 do not change significantly (Figures 5A and S9), indicating that the binding of 1 and 2 fails to change their conformations.…”
Section: Chemistryselectsupporting
confidence: 85%
“…The similar effect was observed for F-c-myc-T and F-c-kit2-T G4 under the same conditions, and the respective ΔT m value is 8.9 and 7.5 °C when Circular dichroism (CD) CD spectroscopy is a perfect technique in investigating the secondary structural changes of DNA. [33] Both c-myc and c-kit2 have a positive peak at 264 nm and a negative peak at 241 nm in 10 mM Tris-HCl buffer containing 100 mM K + at pH 7.0 (Figure S9), which belongs to the parallel G4 structure, [34,35] while bcl-2 has an additional shoulder peak at 295 nm (Figure 5A), which is consistent with the reported mixed-type G4 structure. [36] When different concentrations of compounds are added, CD spectra of three G4 do not change significantly (Figures 5A and S9), indicating that the binding of 1 and 2 fails to change their conformations.…”
Section: Chemistryselectsupporting
confidence: 85%
“…A large number of small heterocyclic molecules have been synthesized and evaluated for their ability to interact with G‐quadruplexes . Among them are the 1,10‐phenanthroline derivatives, such as PhenDC3 and its structural analogues I , tetraaminophenanthroline II , K35, and phenanthroline‐2,9‐bistriazole III (Figure ) . These compounds have been investigated for their capacity to bind and stabilize various G4 topologies and for their selectivity for G‐quadruplex versus duplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Among them are the 1,10-phenanthroline derivatives, such as PhenDC3 and its structurala nalogues I,t etraaminophenanthroline II,K 35, and phenanthroline-2,9-bistriazole III (Figure 1). [17][18][19][20][21][22][23][24][25][26][27][28] These compounds have been investigated for their capacity to bind and stabilize various G4 topologies and for their selectivity for G-quadruplex versus duplexs tructures.…”
Section: Introductionmentioning
confidence: 99%
“…c-MYC oligomer folds into a typical parallel-type G4 structure in a buffer solution containing K + ions as suggested by its characteristic CD signature containing a positive band at 264 nm and a negative minimum at 240 nm (Figure 4b). [39] Upon titration with the ligand Car-DPA (molar ratios of ligand/c-MYC ranging from 0 : 1 to 10 : 1), the positions of the positive and negative bands seemed to be stable, while a decrease in the molar ellipticity to a lesser extent. This suggested that the G4 structure retained the parallel topology.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the binding event, highlighting the morphological change induced by ligand binding to the chiral G4 structure, circular dichroism (CD) titration experiment was conducted. c‐MYC oligomer folds into a typical parallel‐type G4 structure in a buffer solution containing K + ions as suggested by its characteristic CD signature containing a positive band at 264 nm and a negative minimum at 240 nm ( Figure 4 b ) [39] . Upon titration with the ligand Car‐DPA (molar ratios of ligand/ c‐MYC ranging from 0 : 1 to 10 : 1), the positions of the positive and negative bands seemed to be stable, while a decrease in the molar ellipticity to a lesser extent.…”
Section: Resultsmentioning
confidence: 99%